Antimicrobial resistance and molecular detection of extended-spectrum ß-lactamase (ESBL)-producing Escherichia coli in municipal wastewater in Marrakech - Oumaima El garraoui; Amal Loqman; Fatima-Ezahra Amouat; Said Hasnaoui; Nabila Soraa; Souad Loqman (PLoS ONE, 2025)
Extended-spectrum β-lactamase-producing Escherichia coli (ESBL-EC) poses a major threat to public health. However, its environmental dissemination, especially through wastewater, remains insufficiently addressed. This paper examines the presence of ESBL-EC in composite influent and effluent samples from Marrakech’s wastewater treatment plant. Samples were screened on selective agar and isolated strains were identified by MALDI Biotyper® Sirius System. The sensitivity of bacteria to antibiotics was determined by disk diffusion method and phenotypic tests were conducted to detect ESBL production. Molecular identification was characterized by PCR and DNA sequencing. From a total of 72 wastewater samples, 364 resistant Enterobacteriaceae isolates were recovered, of which 134 were confirmed as ESBL-EC, with 78.35% exhibiting multidrug resistance (MDR) phenotypes. The blaCTX-M gene was the most prevalent among isolates obtained from influent samples, followed by blaTEM at 81.25% and blaSHV at 16.67%. Although biological treatment reduced the number of ESBL-EC isolates harboring resistance genes, a significant proportion remained detectable in the final effluent, even after UV disinfection, highlighting the limited efficacy of standard treatment processes in eliminating them. These findings underscore the urgent need to enhance wastewater treatment strategies. Implementing advanced technologies, such as membrane filtration or ozonation, combined with routine monitoring, is critical to reduce the environmental release of resistant bacteria and mitigate their public health risks.